Development of Curriculum Materials for Problem-Based Learning in English Language Education - Rizka Utami; Risma Artika Magfiroh (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study focuses on the development of curriculum materials for implementing Problem-Based Learning (PBL) in English language education. As globalization increases, English proficiency has become essential in various sectors, emphasizing the need for innovative teaching approaches like PBL. PBL encourages active student participation by solving real-world problems, fostering critical thinking, collaboration, and communication skills. However, integrating PBL into English curriculums poses challenges, including resource limitations, lack of teacher training, and assessment complexities. This research explores curriculum design strategies, leveraging technology for enhanced learning, and addressing cultural diversity to ensure effective PBL application. By addressing these challenges, the study aims to offer practical insights for educators to optimize PBL in English language instruction.